Estudo da diversidade genética em Cattleya forbesii Lindi. (Orchidaceae), propagadas in vitro, utilizando isoenzimas - Claudino, Leticia Oliveira (2011)
Current analysis establishes a methodology for the study of Esterase (EST; EC 3.1.1.1), Malato Dehydrogenase (MDH; EC 1.1.1.37) and Isocitrate Dehydrogenase (IDH; EC 1.1.1.42) by PAGE (Polyacrylamide Gel Electrophoresis) system to investigate the genetic diversity in C. forbesii shoots formed from in vitro germinated seeds. Different extraction and fractioning conditions were tested for the three isoenzyme systems. In the case of extraction, the most adequate condition occurred when plant samples were macerated whole and extraction solution prepared with 5 % PVP-40. The most adequate condition for studying α- and β-esterases in C. forbesii occurred by fractioning in polyacrylamide gel 12 % during 6 h and 30 minut. The best fractioning in the case of isoenzymes MDH and IDH, occurred in starch gel 16 % prepared with a buffer with citric acid 0.04M titred with morpholine [N-(3-AMINOPROPYL)-MORPHOLINE] for pH 7.5 at a 60 V voltage at the gel extremities during 14 h. Ten loci (seven for EST, two for MDH and one for IDH) were identified within the context of standardized conditions. This provided an 80 % polymorphism for the C. forbesii population under analysis. Mean number of alleles per locus and per polymorphic locus for C. forbesii were respectively 3.1250 and 2.5788. Alleles of seven of the eight loci analyzed were not distributed according to Hardy-Weinberg equilibrium. Only locus Mdh-1 maintained the equilibrium. Mean Fis value for the eight loci analyzed was 0.2870 and indicated heterozygote deficit in the population. Since excess of heterozygotes has been reported for loci s-Mdh and mt-MDH , this fact suggested a physiological significance for such a condition. The genetic basis of the plants grown from seeds germinated in vitro with KC medium was broad (80 % polymorphism) and indicated that in vitro culture may produce orchids with an extensive genetic variety. Germination system and in vitro culture of C. forbesii seeds failed to establish selection pressure that may indicate a decrease in the species's genetic diversity. The system may be adequate to produce shoots for stock reposition to be cultivated in nature or for preferential crossings to stimulate the production of hybrids in improvement programs.